The conditional mood in the Ruthenian language of V. Tyapinski’s Gospel ca. 1580 - Смирнова, Екатерина Андреевна Андреевна (Slavistica Vilnensis, 2016)
This study traces the evolution of conditionals in the Ruthenian literary language basing on V. Tjapinski’s Gospel, printed around the year of 1580 (further on TG). The Ruthenian language evolves from a living language and changes together with it. Here I dwell upon the variation of the conditional. The article represents the reconstructed paradigms with different variants of the use of conditionals in TG. A table shows the use of language models, analogous to Polish, in the Ruthenian language. The verb forms that emerged under the Polish influence are rare in TG and the most distant from the Old Russian language.